Assistance for the Development of Game-Based Learning Media in the New Normal Era for Teacher of MTs Negeri 9 Jember - Arika Indah Kristiana; Niswatul Imsiyah; Titin Kartini (Pancaran Pendidikan, 2022)
During the COVID-19 pandemic, educators must ensure that teaching and learning activities continue, even though students are not in school. The solution is that educators are required to design online learning as an innovation in the use of technology. Learning at MTs Negeri 9 Jember during the COVID pandemic was carried out using the WA group, google classroom, or google meet. The learning media used by educators at MTs Negeri 9 Jember include powerpoints, videos, pictures (photos). The learning media used by MTs Negeri 9 educators are not effective and less attractive. The media used so far have not involved students to take an active role in the learning process. Therefore, training activities for the development of effective and interesting learning media are needed. One form of interesting learning media is game-based learning media in which there are many choices so that teachers just use it based on the materials to be presented. This community service activity is carried out in the form of training, and assistance by applying a modified Learning Cycle (3E) learning model, which consists of Exploration, Explanation, and Elaboration. Through this activity, partner school teachers are expected to (1) be able to innovate in carrying out classroom learning by utilizing ICT (2) improve the ICT capabilities of partner teachers with many partner teachers developing game-based learning media